Mengurangi perilaku impulsif pada anak attention-deficit hyperactivity disorder dengan teknik reprimand dan token economy - Faizah Faizah (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
One  of the  dominant symptoms of Attention-Deficit  Hyperactivity  Disorder (ADHD) is the  presence of impulsive behavior which is a condition  of failure to control impulses to take certain actions. The assessment methods used were  clinical interviews, observation, The Wechsler Intelligence Scale for Children  (WISC) and  Indonesian ADHD Rating  Scale (IARS) tests. The intervention provided is behavior modification  with reprimand and  token  economy techniques to reduce the behavior  of taking other people’s goods  without permission and forming behavior  asking  for permission. The results  of the intervention showed a decrease in the subject’s impulsive behavior  and the formation of new behavior, namely  asking  for permission